Medication Use During Pregnancy and Breastfeeding: Awareness and Perceptions among Libyan Women - Alzaydani, Marwa Najib Saleh; Abdelrahman, Riad Mohammed; Mohamad, Khalid A. (British Journal of Healthcare and Medical Research, 2025)
Pregnancy is a distinct physiological state in which medication use presents both challenges and concerns due to altered drug pharmacokinetics. In this study, we aimed to evaluate the awareness and perceptions of medication use during pregnancy and breastfeeding among Libyan women. This was a cross-sectional study, questionnaire-based study conducted between September 2024 and March 2025. Of 227 sample a total of 193 women with response rate 82% were included in the final analysis. Out of total, 82% were under the age of 45, and 98% had some level of education. Approximately 53% reported significantly taking medication at least once a week during pregnancy. While 76% either agreed or partially agreed that all medications should be avoided during pregnancy, 28% acknowledged an increase in medication use during this period. 72% believed that medications taken during pregnancy are more harmful than beneficial, and 98% stated that they follow prescribed treatments. Notably, 83% perceived medication use in early pregnancy as harmful or potentially harmful. Women aged 26–45 and those with bachelor’s degrees were more likely to believe herbal medicines are safe with P-values = 0.017 and 0.001, respectively, while women with postgraduate education disagreed with this view P-value = 0.97. Regarding specific medications, 54% reported using medication for heartburn or gastritis, 39% used antibiotics. 10% used Asthma/Allergy medications, with significant associations among participants with public education and bachelor’s degrees P-value=0.001 and 0.03, respectively. The primary source of information for 93% of the participants was physicians, while 23% consulted pharmacists. Age and educational background were strongly linked to perceptions of herbal remedy safety. Overall, medication and herbal remedy use among Libyan pregnant and breastfeeding women, as well as their safety perceptions, were closely associated with age and educational background.